Metabolic analysis of efficient methane production from food waste with ethanol pre-fermentation using carbon isotope labeling. (November 2019) - Zou, Hui; Gao, Ming; Wang, Qunhui; Zhang, Wenyu; Wu, Chuanfu; Song, Na
Highlights: We investigated metabolic processes underlying anaerobic digestion of food waste. Using carbon isotope labeling, we quantified carbon flow in anaerobic digestion. Ethanol pre-fermentation significantly enhanced anaerobic digestion. Our results would improve our theoretical understanding of anaerobic digestion. Abstract: Anaerobic digestion (AD) has been widely applied as an economic option for food waste (FW) treatment. In this study, the group treated with ethanol pre-fermentation (EP) for 12 h (EP12) exhibited the highest cumulative biogas yield (206 mL/g-volatile solid) during AD process and therefore it was used to illuminate the underlying metabolic processes of AD with EP. Carbon isotope labeled glucose was supplemented to FW substrate, and the EP process was found to alleviate the acidification inhibition with conducting extremely high carbon flux towards ethanol formation (43.7%). Then an efficient acetogenesis phase was also observed in EP12 group, because of high carbon conversion rate from ethanol to acetate. Overall, higher carbon conversion rate to methane (90.1%) during methanogenesis was found in the AD system with EP than in the control experiment (80.3%). Thus, we quantitatively confirmed that EP affects the AD metabolism of FW in terms of carbon flow distribution.